Evolutionary Patterns of Collagen Fiber Arrangement and Calcification in Atherosclerosis - Chunyang Ma; Zhenzhen Jia; Shuaiyin Liu; Xiangyi Liao; Hongyan Kang; Xufeng Niu; Yubo Fan (Research)
Collagen is a major structural component of human tissues, and its spatial arrangement is critical for maintaining tissue mechanical integrity and regulating cell behavior. In atherosclerosis (AS), collagen fiber arrangement has been implicated in plaque stability and the regulation of vascular calcification, yet its evolution during disease progression and association with other pathological processes remain poorly understood. In this study, male ApoE−/− mice were fed a high-fat diet to establish a model of AS. Histological staining was performed every 5 weeks to analyze the collagen fiber alignment in the aortic arch of mice, along with calcification-related cells, proteins, and growth factors. The experimental results indicate that collagen fiber arrangement underwent gradual disruption and randomization as the disease progressed. Randomized collagen fibers were found to colocalize with inflammatory infiltration, smooth muscle cell phenotypic switching, osteogenic gene expression, and calcification. Therefore, changes in collagen fiber arrangement can be used to determine the presence of AS lesions, delineate their location, monitor disease progression, and assess plaque stability, thereby providing a solid theoretical foundation for the diagnosis and treatment of AS.